The Territoriality of South Africa's Employment Legislation and the Jurisdiction of the Labour Court in Cross-Border Employment: A Comparative Analysis - Schoeman, Elsabe (University of Pretoria, 2022)
Dissertation (LLM)--University of Pretoria, 2022